Determinan penggunaan aplikasi mobile JKN terhadap generasi muda - Putri Widya Ningsih; Dwi Noerjoedianto; Adila Solida; Rumita Ena Sari (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: The development of digital technology in healthcare has prompted the Social Security Agency to introduce the Mobile JKN application as an innovation to facilitate public access to healthcare services. However, the application's utilization among adolescents remains suboptimal, despite the younger generation being a group familiar with digital technology. Purpose: To analyze the determinants of Mobile JKN application usage among the younger generation. Method: Quantitative research with a cross-sectional approach. The population in the study were students of Batanghari 5 State Senior High School in the 2025/2026 academic year. The research sample consisted of 110 respondents selected using a stratified random sampling technique. Data collection was carried out using a questionnaire based on the Technology Acceptance Model (TAM) theory. Data analysis was carried out univariately and bivariately using the chi-square test and Fisher Exact Test. Results: The study showed that 68.2% of respondents used the Mobile JKN application. There was a significant relationship between perceived usefulness and Mobile JKN application usage (p-value = 0.000; PR = 2.895), as well as a significant relationship between intention to use and Mobile JKN application usage (p-value = 0.000; PR = 5.613). Meanwhile, perceived ease of use (p-value = 0.206) and attitude toward use (p-value = 0.262) were not significantly associated with the use of the Mobile JKN application. Conclusion: Perceived usefulness and intention to use are significantly associated with the use of the Mobile JKN application among the younger generation. Keywords: Mobile JKN; Perceived Usefulness; Technology Acceptance Model; Usage Intention; Young Generation.